Optimization of Production Amount Using Newsboy Model and Raw Material Control Planning Using Material Requirement Planning (MRP) - Bagus Ismail Adhi Wicaksana; Erni Suparti (Universitas Muhammadiyah Sidoarjo, 2018)
A company have to do inventory control for available guarantying of material, component or item at the time to fulfill production schedule, and available guarantying of product become to consumer and take care of inventory at minimum condition. As object of research is CV. Cita Nasional located in Salatiga. Problems that exist in the CV. Cita Nasional often experience shortages of raw materials caused by internal and external factors. The approach taken to solve this problem by making a production plan using the Newsboy Problem because milk products including perishable product and raw material inventory planning (MRP). From the calculation results obtained the company must produce optimal demand every Monday to Sunday. While the raw material inventory plan using Economic Order Quantity (EOQ) method. Company decreased cost for fresh milk amounting to Rp.35.526.780 and decreased raw material expense cost for whey powder amounting to Rp. 22.573.650.